Functional brain imaging in the clinical assessment of consciousness. - Michael S Rafii (Public Library of Science (PLoS), 2010)
Recent findings suggest that functional brain imaging might be used to identify consciousness in patients diagnosed with persistent vegetative state and minimally conscious state. Michael Rafii and James Brewer discuss the potential for fMRI's wider implementation in clinical practice, and associated caveats.